Distrust, accountability and capacity in South Africa's fragmented eduction system - Chilenga-Butao, Thokozani; Pakade, Nomancotsho (Taylor & Francis Group, 2020)
South Africa's current basic education system is a product of the apartheid education bureaucracy that was fractured along racial lines, and later significant efforts to amalgamate this fragmented system into a single, inclusive and equal system. This chapter demonstrates how negative apartheid legacies of distrust and a lack of both accountability and capacity took root in apartheid's oppressive and unequal system, as well as efforts by the Department of Basic Education to overturn these legacies in the democratic era. The central argument of this chapter is that, despite formal bureaucratic procedures, expressed through regulations, which should produce more capacity and accountability in the education system, there are also codified practices of governance at the provincial and district levels that produce different outcomes from the intended goal of improved education. This argument is illustrated through a case study of the Schools Rationalisation Project in the Eastern Cape province, South Africa.
This chapter highlights the challenges of accountability and capacity in PEDs of education, specifically in the province of the Eastern Cape. This province underwent a process referred to as the School Rationalisation Project (SRP) which sought to facilitate an accessible and better resourced schooling system through the eradication of small and unviable schools. After some internal reflections and several attempts to rationalise in the province, the Eastern Cape Department of Education requested support from the Government Technical and Advisory Centre (GTAC) to assist with the SRP.
Keywords: Education; South Africa; Constitution of the Republic of South Africa; Provincial Education Departments (PEDs); Eastern Cape Department of Education; School Rationalisation Project (SRP); Government Technical and Advisory Centre (GTAC); South African education system; SDG-4: Quality education